Financial Literacy Education for Students of Learning Center At-Tanzil Ampang Kuala Lumpur, Malaysia - Ilza Febrina; Lela Nurlaela Wati; Ramdany Ramdany; Ahmad Darda; M. Lutfi; Budi Andru; Octavia Handayani; Ade Irma Rismala; Mita Apriliasari (International Journal of Community Engagement and Development, 2023)
The Financial Services Authority (OJK), in collaboration with the ministries and Financial Services Institutions, continues to synergize efforts in the "Let's Save" campaign. This initiative is part of the government's commitment to enhance financial literacy among the public and foster a savings culture from an early age. Therefore, financial literacy education is deemed necessary at the early childhood education level, both domestically and internationally. As part of this educational outreach, financial literacy education was provided to students at one of the learning centers, namely sanggar belajar (SB) At Tanzil Ampang Malaysia, under the coordination of the Indonesian School Kuala Lumpur, Malaysia. The objective of this activity is to increase awareness and understanding among children regarding the significance of early savings, instill good financial habits, and enable them to identify and distinguish between wants and needs. The methodology employed involves lectures on the importance of early savings and interactive question-and-answer sessions. The participants exhibited great enthusiasm throughout the program. This Community Service Program yields benefits for the students, as possessing knowledge of sound financial literacy is expected to encourage a desire for savings intensely within their minds and reflect in their daily behaviour.